2014
DOI: 10.3832/ifor0911-007
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific climate response of oaks (Quercus spp.) under identical environmental conditions

Abstract: © iForest -Biogeosciences and Forestry IntroductionAn increase in pest and disease outbreaks as well as projected climate warming constitutes a serious threat to forestry over the coming decades (Bolte et al. 2009, Sturrock et al. 2011. As a consequence of these impacts, individually or in combination, tree vitality and survival may decline resulting in reduced productivity (Leuzinger et al. 2005). The resilience of species to biotic and abiotic stresses, as well as their adaptation potential to changing envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 48 publications
2
11
0
1
Order By: Relevance
“…Our results also showed that the co-occurrence of Fraxinus oxycarpa and Quercus petraea, both associated with peculiar ecological conditions (Temunović et al 2012, Sanders et al 2014 seems to promote distinct assemblages of EMF and Sh fungi, as compared with other woody species. As a consequence, strategies for the conservation of fungi should aim at retaining diverse assemblages of host species and different structures across forests.…”
Section: Agaricus Fuscofibrillosussupporting
confidence: 56%
“…Our results also showed that the co-occurrence of Fraxinus oxycarpa and Quercus petraea, both associated with peculiar ecological conditions (Temunović et al 2012, Sanders et al 2014 seems to promote distinct assemblages of EMF and Sh fungi, as compared with other woody species. As a consequence, strategies for the conservation of fungi should aim at retaining diverse assemblages of host species and different structures across forests.…”
Section: Agaricus Fuscofibrillosussupporting
confidence: 56%
“…The positive significant correlations between precipitation and tree-ring width or between RSMC and tree-ring width predominate (e.g. Mérian et al, 2011;Petráš & Mecko, 2011;Michelot et al, 2012;Gillner et al, 2013;Sanders et al, 2014;Rybníček et al, 2015). A negative effect of summer temperatures on tree-ring width has been reported in other European areas, such as France (Michelot et al, 2012), Germany (Gillner et al, 2013), Slovakia (Petráš & Mecko, 2011), and Austria, Hungary, Slovenia, Croatia and Serbia (Čufar et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Case studies in specific small areas have seldom been performed (e.g. Sanders et al, 2014), and never in the Czech Republic.…”
Section: Introductionmentioning
confidence: 99%
“…В цілому середній радіальний приріст дубів «Феофанії» (табл. 1) узгоджується з приростом лісових культур дуба звичайного, створених та відновлених у 50-ті роки в південно-східній Англії, значення якого становить 2,37±0,43 мм [SANDERS et al, 2014]. Схожий темп радіального росту дуба звичайного і в інших країнах Європи.…”
Section: результати досліджень та їх обговоренняunclassified